PERAN TEKNOLOGI FINANSIAL BAGI PEREKONOMIAN NEGARA BERKEMBANG - Ilman, Abdul Hadi; Noviskandariani, Gita; Nurjihadi, Muhammad (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2019)
The emergence of financial technology is rooted from developed countries with established infrastructure, sophisticated technology, and more digital society. While this is not the case for developing countries, fintech has found difficulties in penetrating developing countries and improving their financial inclusion. This research aims to find fintech best practices around the world and analyze how they could improve the economic life of people in developing countries. We divided into three main category of problems that fintech could contribute and give solution: lack of infrastructure, less digital society, and chaotic and informal society. Then we analyzed three fintechs represent the three categories: Flutterwave, Creditfix, and Malako. We found that these fintechs have been able to contribute to financial inclusion and economy because of these reasons: 1) the ability to find what people really need; 2) the ability to simplify the sophisticated and complex technology behind the simple product; and 3) the ability to collaborate with traditional financial service.